2017
DOI: 10.3389/fpsyt.2017.00079
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Conferring Glutamatergic Genes and Brain Glutamate Plus Glutamine in Schizophrenia

Abstract: BackgroundThe proton magnetic resonance spectroscopy (1H-MRS) signals from glutamate (or the combined glutamate and glutamine signal—Glx) have been found to be greater in various brain regions in people with schizophrenia. Recently, the Psychiatric Genetics Consortium reported that several common single-nucleotide polymorphisms (SNPs) in glutamate-related genes confer increased risk of schizophrenia. Here, we examined the relationship between presence of these risk polymorphisms and brain Glx levels in schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
6
10
0
1
Order By: Relevance
“…The finding of common genetic influences on glutamate levels in the thalamus and disease in our study is supported by a report of higher glx levels in the thalamus of subjects at increased familial risk for schizophrenia [33], and a recent study linking higher glx levels to glutamate-related genes associated with risk for schizophrenia [5]. The current heritability estimates are in line with the heritability estimate of glx in the thalamus reported in a twin study in children with autism and controls [34], suggesting a generalizability of the heritability estimate across populations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The finding of common genetic influences on glutamate levels in the thalamus and disease in our study is supported by a report of higher glx levels in the thalamus of subjects at increased familial risk for schizophrenia [33], and a recent study linking higher glx levels to glutamate-related genes associated with risk for schizophrenia [5]. The current heritability estimates are in line with the heritability estimate of glx in the thalamus reported in a twin study in children with autism and controls [34], suggesting a generalizability of the heritability estimate across populations.…”
Section: Discussionsupporting
confidence: 88%
“…Schizophrenia constitutes a heterogeneous phenotype with a complex etiology, but clinical, animal, and genetic studies have supported the involvement of glutamate metabolism in its pathophysiology [1][2][3][4][5]. However, the extent to which aberrant glutamate concentration and disease liability are founded in common genes remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…These observations have been reported in patients with SCZ, especially in subjects at risk of psychosis [178].…”
Section: Genetic Associations Between Cav Genes and Psychiatric Disorsupporting
confidence: 72%
“…Another QTL window at 19.9-20.9 Mb, which accounted for 0.87% of additive genetic variance, contained SLC38A7, which encodes solute carrier family 38 member 7 (also known as the SNAT7 protein). Hägglund et al reported that SLC38A7 is a sodium-coupled amino acid transporter in glutamatergic neurons in the brain 40 , and it has been implicated as a risk-conferring glutamatergic gene in schizophrenia 41 . In the QTL region of SSC6:70.8-71.8 Mb, the mammalian target of rapamycin (mTOR) gene was found to be associated with SGE on ADG.…”
Section: Gwas Of Sge and Dge On Adg Sge On Adgmentioning
confidence: 99%